Tradução anotada, autor-tradutor invisível: Richard Francis Burton na Brasiliana - Rodrigues, Cristina Carneiro (TradTerm, 2010)
The aim of this paper is to analyze the translation of the work by the translator-traveller Richard Francis Burton, Explorations of the Highlands of the Brazil, with a full account of the gold and diamond mines, made by Américo Jacobina Lacombe, trying to relate the work of the latter to the editorial goals of the Brasiliana Collection. As a subseries of the Biblioteca Pedagógica Brasileira [Brazilian Pedagogical Library] published by Companhia Editora Nacional, Brasiliana was conceived in agreement with the 1930s and 1940s policies to expand lay education and make it possible for Brazilians to get to better know the greatness of their country. The paper will focus on the numerous translator’s notes, since many of them reveal Lacombe’s didactic purpose of informing readers about Brazilian history and geography. The analysis also examines the effacement of Burton’s translations from Portuguese into English in his book.